The effects of SQDNs properties coated by potassium / Noor Aida Roslan - Roslan, Noor Aida (2011)
Silicon Quantum Dots nano particles (SQDNs) were formed by grinding the free standing of Porous silicon that have been formed by anodically etching p-type Si [100] wafer in hydrofluoric (HF) solution at 1:1 ratio of ethanol with increase current density to 50 mA/cm2. The samples were prepared by coating to different concentration of potassium which is 0.6 M, 0.8 M and 1.0 M. The samples were characterized by using SEM, UVVis, FTIR spectrometer and PL spectrometer. The Potassium was successful coated into SQDNs. The samples were immersed in 30 ml distilled water to investigate the Potassium absorption in SQDNs wash for four batches. The UV-Vis result show that more quantity of K release from SQDNs for 1st wash batch for all concentration. The FTIR spectrum show the amount of KNO3 released after wash for four batches. The coating SQDNs with KNO3 show the wavelengths shifted to longer on the PL intensity.